Respuesta :
5-5y=0
-5y=-5
y=1
4x-6y= -18 (sub y=1)
4x-6(1)=-18
4x-6=-18
4x=12
x=3
4x-6y= -18 (sub in x=3 to find y)
4(3)-6y=-18
12-6y=-18
-6y=-30
y=5
Therefore, the solution of the two equations is x=3 and y=5!! :)
-5y=-5
y=1
4x-6y= -18 (sub y=1)
4x-6(1)=-18
4x-6=-18
4x=12
x=3
4x-6y= -18 (sub in x=3 to find y)
4(3)-6y=-18
12-6y=-18
-6y=-30
y=5
Therefore, the solution of the two equations is x=3 and y=5!! :)
Answer:
y=1, x=-3
Step-by-step explanation:
Isolate y for 5-5y=0
5-5y=0
Subtract 5 from both sides
5-5y-5=0-5
Simplify:
-5y=-5
Divide both sides by -5
-5y/-5=-5/-5
Simplify
y=1
Substitute y=1
4x-6*1=-18
Simplify
4x-6*1=-18
Simplify 4x-6*1
4x-6=-18
Add 6 to both sides:
4x-6+6=-18+6
simplify
4x=-12
Divide both sides by 4
4x/4=-12/4
Simplify
x=-3
The solutions to the system are
y=1, x=-3